Plastidic phosphoglucose isomerase is an important determinant of starch accumulation in mesophyll cells, growth, photosynthetic capacity, and biosynthesis of plastidic cytokinins in Arabidopsis - Bahaji, Abdellatif; Sánchez-López, Ángela M; De Diego, Nuria; Muñoz, Francisco J; Baroja-Fernández, Edurne; Li, Jun; Ricarte-Bermejo, Adriana; Baslam, Marouane; Aranjuelo, Iker; Almagro, Goizeder; Humplík, Jan F; Novák, Ondřej; et al. (PLoS One, 2015)
Phosphoglucose isomerase (PGI) catalyzes the reversible isomerization of glucose-6-phosphate and fructose-6-phosphate. It is involved in glycolysis and in the regeneration of glucose-6-P molecules in the oxidative pentose phosphate pathway (OPPP). In chloroplasts of illuminated mesophyll cells PGI also connects the Calvin-Benson cycle with the starch biosynthetic pathway. In this work we isolated pgi1-3, a mutant totally lacking pPGI activity as a consequence of aberrant intron splicing of the pPGI encoding gene, PGI1. Starch content in pgi1-3 source leaves was ca. 10-15% of that of wild type (WT) leaves, which was similar to that of leaves of pgi1-2, a T-DNA insertion pPGI null mutant. Starch deficiency of pgi1 leaves could be reverted by the introduction of a sex1 null mutation impeding β-amylolytic starch breakdown. Although previous studies showed that starch granules of pgi1-2 leaves are restricted to both bundle sheath cells adjacent to the mesophyll and stomata guard cells, microscopy analyses carried out in this work revealed the presence of starch granules in the chloroplasts of pgi1-2 and pgi1-3 mesophyll cells. RT-PCR analyses showed high expression levels of plastidic and extra-plastidic β-amylase encoding genes in pgi1 leaves, which was accompanied by increased β-amylase activity. Both pgi1-2 and pgi1-3 mutants displayed slow growth and reduced photosynthetic capacity phenotypes even under continuous light conditions. Metabolic analyses revealed that the adenylate energy charge and the NAD(P)H/NAD(P) ratios in pgi1 leaves were lower than those of WT leaves. These analyses also revealed that the content of plastidic 2-C-methyl-D-erythritol 4-phosphate (MEP)-pathway derived cytokinins (CKs) in pgi1 leaves were exceedingly lower than in WT leaves. Noteworthy, exogenous application of CKs largely reverted the low starch content phenotype of pgi1 leaves. The overall data show that pPGI is an important determinant of photosynthesis, energy status, growth and starch accumulation in mesophyll cells likely as a consequence of its involvement in the production of OPPP/glycolysis intermediates necessary for the synthesis of plastidic MEP-pathway derived hormones such as CKs.
Keywords: mutace; Genetic Loci; Metabolic Networks and Pathways; Phenotype; Mesophyll Cells; glukosa-6-fosfátisomerasa; Arabidopsis Proteins; škrob; listy rostlin; metabolické sítě a dráhy; cukerné fosfáty; Photosynthesis; erythritol; Plant Leaves; Glucose-6-Phosphate Isomerase; Mutation; Sugar Phosphates; fotosyntéza; cytokininy; Cytokinins; proteiny huseníčku; mezofylové buňky; Starch; alely; Erythritol; Alleles; Arabidopsis; fenotyp; genetické lokusy